Contrast sensitivity and orientation selectivity in lamina IV of the striate cortex of Old World monkeys. - Hawken, M; Parker, A (1984)
Contrast sensitivity and orientation selectivity were measured for neurons in lamina IV of macaque striate cortex. Contrast sensitivity was determined for a range of spatial frequencies, using a staircase method. The stimuli were at the optimal orientation, direction and speed of drift for each neuron. The assignment of each recording site to a subdivision of lamina IV was made by histological reconstruction of each electrode penetration from sections reacted for cytochrome oxidase and stained for Nissl substance. Neurons in the magnocellular recipient zone of IVc (IVc alpha) have high contrast sensitivities, while those in the parvocellular recipient zone (IVc beta) have low contrast sensitivities. Both of the upper subdivisions of lamina IV (IVa and IVb) contain a mixture of neurons with high and low contrast sensitivities. There were orientation selective neurons within all subdivisions of lamina IV, even in IVc, whereas non-oriented neurons were found only in those subdivisions that receive a direct parvocellular geniculate input (IVa and IVc beta).